Outsourcing without Cost Advantages - Chrysovalantou Milliou (Center for Economic Studies and ifo Institute (CESifo), 2023)
This paper explores why competing firms can choose to outsource to an external common supplier that does not have a cost advantage in input production. The supplier, through its contract offers, manages to generate asymmetry, to alter product market competition, and to extract profits from the competing .rms. Two-part tariffs and sequential contracting are both crucial for the emergence of outsourcing. The supplier purposefully avoids industry pro.t maximization to enlarge its profits share. Both consumer and total welfare benefit from the presence of an otherwise redundant supplier in the market.
Keywords: D43; L11; L22; L23; L24; 330; outsourcing; strategic outsourcing; make-or-buy; two-part tariffs; common supplier; sequential contracting